Effect of thermal annealing on the luminescent characteristics of CdSe/ZnSe quantum dot heterostructure - Borkovska, L.V.; Stara, T.R.; Korsunska, N.O.; Pechers’ka, К.Yu.; Germash, L.P.; Bondarenko, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Effect of post-growth thermal annealing within the temperature range 200 to 430 ºC for 15 min on the luminescent characteristics of CdSe/ZnSe quantum dot (QD) heterostructure was studied. Annealing at lower temperatures (Tann <= 270 ºС) results in an increase by a factor of 2-3 of the intensity of two photoluminescence bands observed, the first being caused by excitonic transitions in QDs and the second one being connected with the defect complex including a column II vacancy. The effect is supposed to be caused by annealing of as-grown nonradiative defects. Annealing at higher temperatures (Tann > 270 ºС) stimulates a decrease of the QD photoluminescence band intensity and up to 100 meV blue shift of its peak position. The former is explained by generation of extended defects and reduction of the QD density. The blue shift observed at 370-430 ºС is ascribed to diffusion of cadmium from QDs that also results in reduction of the QD density. It is found that the energy of excitonic transitions in the wetting layer does not change upon annealing. Lower thermal stability of QDs as compared to that of the wetting layer has been explained by strain-enhanced lateral Cd/Zn interdiffusion via vacancies. The presence of column II vacancies in the wetting layer is proved by characteristics of defect-related PL band and its excitation spectra.